Clumped isotope geochemistry of carbonatites in the north-western Deccan igneous province: Aspects of evolution, post-depositional alteration and mineralisation. (1st April 2020) - Fosu, Benjamin R.; Ghosh, Prosenjit; Viladkar, Shrinivas G.
Abstract: Carbonatites crystallise along a wide range of solidus temperatures and are commonly affected by post-magmatic textural re-equilibration and diagenesis. Further insights into the formation and modification of carbonatites are provided using carbon, oxygen and clumped isotope (Δ47 ) data of rocks from spatially associated Amba Dongar and Siriwasan alkaline complexes in the north-western Deccan igneous province, India. We derive apparent equilibrium blocking temperatures to help constrain the thermal evolution of the different rock types found within the alkaline complexes in a petrographic context. The apparent temperatures for the carbonatites are significantly low but are consistent with reports on other global carbonatites and model predictions. Rapidly cooled Oldoinyo Lengai natrocarbonatite yielded similar low temperatures, even in the absence of bulk isotopic alteration. The isotopic proxies and petrographic observations favour both isotopic exchange reactions and diagenesis in altering Δ47 values in calciocarbonatites. Diagenetic reactions are however strongly favoured, as secondary calcites in nephelinites and ferrocarbonatites record much lower temperatures than in the calciocarbonatites, highlighting the effect of fluids and diagenetic reactions in 13 C 18 O bond ordering in carbonatites. Variations in the CO isotope data reveal the coupling of fractional crystallisation and post-magmatic fluid-rock interactions on bulk rock composition. After emplacement, the resetting of clumped isotope signatures in carbonatites is facilitated by post-magmatic processes in both open and closed systems.